Manajemen Kepemimpinan Situasional Kepala Madrasah Dalam Meningkatkan Profesinalisme Guru (Studi Kasus Di Madrasah Ibtidaiyah Ma’arif 01 Kh. Shiddiq Jember) - Ilmi, Ach. Faridul; Turmudi, Imam (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
The situational leadership style of the madrasah principal, especially in improving the professionalism of teachers at MIMA 01 KH. Shiddiq Jember, Gebang Purworejo, who is required to make continuous efforts to improve the quality of his education. The leadership is carried out with reference to the improvement program so that the teacher's professional attitude is realized in carrying out his duties and responsibilities. The purpose of this study is to describe the implementation of situational leadership of madrasah principals with four indicators of leadership style, namely telling style, selling style, participating style, and delegating style, as an effort to improve teacher professionalism. This research was conducted with a qualitative approach. The subjects of this study were principals, teachers, and students. Data collection techniques from this study used the methods of observation, interviews, and documentation. The results of this study indicate that, the head of MIMA 01 KH. Shiddiq Jember has implemented a situational leadership style that has met four indicators. This is evidenced from the results of the study that: First, the principal has applied the Telling style as evidenced by 1) giving work to the teacher always giving orders, and not being coercive; 2) provide direction before carrying out the work. Second, the madrasa principal has applied the Selling style as evidenced by 1) making clear rules; 2) provide opportunities for teachers to express their opinion; 3) the head of the madrasa applies democracy; 4) can receive suggestions from teachers; 5) provide motivation to subordinates in completing the work; 6) give praise and incentives to the teacher when completing the job well. Third, the principal has implemented a Participating style as evidenced by: 1) the principal is able to make the right decisions in completing the work; 2) the head of the madrasa is active in various activities carried out by the community. Fourth, the madrasah principal has applied the Delegating style, as evidenced by: 1) the madrasah principal monitors the work of the teacher; 2) the head of the madrasa gives full responsibility to the teacher in completing the work.